Early molecular events in the induction phase of contact sensitivity. - Enk, A H (1992)
To assess changes in epidermis-derived cytokine mRNA levels early in the afferent phase of allergic contact sensitivity, total epidermal mRNA was analyzed at various times after painting skin with haptens. We used a sensitive reverse transcriptase-polymerase chain reaction technique to quantitatively compare the regulation patterns of the following mRNAs: class II major histocompatibility complex I-A alpha, tumor necrosis factor alpha (TNF-alpha), interleukin (IL) 1 alpha, IL-1 beta, interferon (IFN) gamma, granulocyte/macrophage colony-stimulating factor, IFN-induced protein 10, and macrophage inflammatory protein 2. Enhanced Langerhans cell-derived IL-1 beta mRNA signals were detected as early as 15 min after skin painting with allergens. TNF-alpha, IFN-gamma, and granulocyte/macrophage colony-stimulating factor mRNAs were found to be upregulated after application of allergens, irritant, and tolerogens, but class II major histocompatibility complex I-A alpha, IL-1 alpha, IL-1 beta, IFN-induced protein 10, and macrophage inflammatory protein 2 mRNAs were upregulated only after allergen painting. Depletion of specific cell populations demonstrated that Langerhans cells were the primary source of the IL-1 beta and class II major histocompatibility complex I-A alpha mRNAs, keratinocytes were the primary source of TNF-alpha, IL-1 alpha, IFN-induced protein 10, and macrophage inflammatory protein 2, and infiltrating T lymphocytes were the source of IFN-gamma. Relevance of the molecular findings was demonstrated by the identification of biologically active IL-1 alpha and immunoreactive TNF-alpha in culture supernatants. These studies demonstrate that Langerhans cell-derived and certain keratinocyte-derived cytokine mRNAs are selectively upregulated by allergens in the very early afferent phase of contact sensitivity.